Possible solutions to the shortcomings of the Yale-Brown Obsessive-Compulsive Scale - Diniz,Juliana (2015)
OBJECTIVE: The Yale-Brown Obsessive-Compulsive Scale is the most frequently used instrument to measure obsessive-compulsive symptom severity. We describe its shortcomings and propose new methods of evaluating current severity and treatment response. METHOD: The Yale-Brown Obsessive-Compulsive Scale total and subscale scores were pooled from one cross-sectional study database containing information on 1,000 obsessive-compulsive disorder patients from seven specialized mental health care centers. Additional longitudinal data were pooled for 155 patients who participated in a 12-week trial that evaluated the effectiveness of fluoxetine vs. cognitive-behavior therapy as first-line treatment options. All patients were followed by a clinician who provided a clinical opinion of improvement. Neither patients nor clinicians were aware of the classifications proposed in this study. New methods for using the severity scores were compared with the clinical opinion of improvement. RESULTS: In the Yale-Brown Obsessive-compulsive scale, the summing-up of subscale scores to compose a total score does not accurately reflect clinical severity. In addition, the reduction of scores with treatment does not usually reach score zero in either subscale. To overcome such problems, we suggest (a) use of the maximum score of any of the subscales; (b) use of a minimum score of 4 in each subscale or 5 for the maximum in any subscale as the goal after treatment. This method performed better than traditional ones regarding sensitivity and specificity against the gold standard represented by the clinical opinion of improvement. CONCLUSION: The new proposed response criteria are coherent with the clinical opinion of improvement and perform better than the traditional methodology.